2020
DOI: 10.1161/str.0000000000000347
|View full text |Cite
|
Sign up to set email alerts
|

Stroke Code Presentations, Interventions, and Outcomes Before and During the COVID-19 Pandemic

Abstract: Background: Anecdotal reports suggest fewer patients with stroke symptoms are presenting to hospitals during the coronavirus disease 2019 (COVID-19) pandemic. We quantify trends in stroke code calls and treatments at 3 Connecticut hospitals during the local emergence of COVID-19 and examine patient characteristics and stroke process measures at a Comprehensive Stroke Center (CSC) before and during the pandemic. Methods: Stroke code activity was analyzed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
93
1
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 89 publications
(110 citation statements)
references
References 18 publications
(18 reference statements)
12
93
1
2
Order By: Relevance
“…Other demographic criteria for exclusion such as NIHSS did not differ, leaving time from symptom onset to 911 alert as the most likely explanation. This is consistent with data from other centers documenting that patients delay calling 911 for emergency conditions because of fear of contracting COVID in the ED or hospital [ 8 , 9 ].…”
Section: Discussionsupporting
confidence: 89%
“…Other demographic criteria for exclusion such as NIHSS did not differ, leaving time from symptom onset to 911 alert as the most likely explanation. This is consistent with data from other centers documenting that patients delay calling 911 for emergency conditions because of fear of contracting COVID in the ED or hospital [ 8 , 9 ].…”
Section: Discussionsupporting
confidence: 89%
“…This analysis has limitations, deriving primarily from the possibility that cerebrovascular events in patients with COVID-19 are underreported, especially in patients in critical clinical conditions but also in asymptomatic or paucisymptomatic patients presenting mild stroke-related symptoms and not evaluated by a neurologist. Another consideration is that many patients are expected to have remained undiagnosed because they did not have access to hospital facilities during the period of greatest pandemic burden (153).…”
Section: Limitationsmentioning
confidence: 99%
“…As people continue to adjust to social distancing, a shift in the epidemiology of stroke and other medical conditions will most likely be observed, as is being seen in myocardial infarction [29] and in other countries [30][31][32][33][34][35][36][37] in the context of acute ischemic stroke. Although there is evidence to suggest a high rate of cerebrovascular complications in patients with SARS-CoV-2 infection [38][39][40][41][42][43], anecdotal reports indicate a falling rate of new ischemic stroke admissions [30][31][32]34,37,[44][45][46][47][48], stroke code activations [30,36,[49][50][51][52][53], imaging numbers [44,45], and diagnoses [45].…”
Section: Decrease In Ischemic Stroke Patientsmentioning
confidence: 99%
“…Persons who are African American, Black, or Latino are contracting SARS-CoV-2 at higher rates and experiencing higher mortality [75][76][77][78], and comorbidities may explain these differences [74]. Due to this increased risk, Black and Hispanic or Latino patients, particularly those without health insurance [52], may avoid medical care. Observations from a telestroke registry in North Carolina reported that a lower percentage of Black patients presented during the pandemic (13.9% versus 29% before the pandemic, P<.001).…”
Section: Disparitiesmentioning
confidence: 99%
See 1 more Smart Citation